Momentum-resolved observations of the phonon instability driving geometric improper ferroelectricity in yttrium manganite - Dipanshu Bansal (Nature Portfolio, 2018)
The improper ferroelectric mechanism of YMnO3 has been difficult to observe directly but is important for understanding its other interesting properties such as multiferroicity. Bansal et al. use neutron scattering and ab initio calculations to show that phonons drive the transition, confirming earlier theories.